MOBILITAS SOSIAL PESANTREN DI INDONESIA - Miftahusyaian, Mohammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
The birth of the Islamic boarding school in the middle of the community, have led this institution has a strong relationship with the community. In fact, often the interplay between boarding school with life and the surrounding environment exceeds the effect of the administrative area of the village or surrounding villages. human resource development for the students should refer to the needs of the community itself, because then the students will return to the community after they finish their studies, the return of the students is expected to be an agent of renewal (agent of change) and build community. At various pesatren in Indonesia, social mobility has happened quite a long time due to their boarding system integration with the public system followed by the developments taking place in the community. The integration of these two systems allows a community to access various economic resources of both. It certainly can be a cause of social mobility. The transition from being a profession of chaplain / counselor religion only later become professional workers such as employers, educators, politicians, and so is the most dominant cause of mobility in schools. Likewise, the development of community schools in terms of both economic and social development of the world of work and marriage among layers cause high mobility both vertically and horizontally. Social mobility in society is strongly influenced by the social system and values that exist therein. A society with a closed system, would not allow for social mobility can occur vertically or horiziontal subsequently leading to the failure of a rearrangement in society.Keywords: Mobility, Islamic boarding school